Photoacoustic imaging algorithm development and simulation - Tao, Pengcheng (Nanyang Technological University, 2023)
Photoacoustic imaging (PAI) is a very promising medical imaging mode developed in recent years. A novel imaging technique that utilizes the photoacoustic effect to capture 2D or 3D images of the internal morphological structure of substances. Compared with traditional medical imaging methods (CT, optical coherence tomography, MRI, ultrasonic imaging, etc.), PAI has its outstanding advantages. It is a non-invasive and nondestructive imaging method with high penetration depth and high image contrast. Among the mode of photoacoustic, acoustic resolution photoacoustic imaging (AR-PAM) is widely applied in medical equipment. In AR-PAM, focused ultrasonic transducer with large numerical aperture is usually used in order to obtain high imaging quality. However, due to the limited focal depth of the transducer, signal-to-noise ratio of photoacoustic image and the lateral resolution will be significantly reduced in the defocus region. The synthetic aperture technology based on virtual points is helpful to solve the problem of the decline of the lateral resolution of AR-PAM in the out of focus region. At present, AR-PAM synthetic aperture focusing technology has developed a variety of algorithms, but its basic algorithm is two-dimensional synthetic aperture focusing. This paper summarizes the basic knowledge of photoacoustic imaging and photoacoustic imaging system, deduces the detailed process of two-dimensional synthetic aperture focusing algorithm, and realizes the algorithm based on MATLAB GUI.